Implementation of TPACK-based problem-based learning model on social studies learning outcomes of elementary school students - Darmawati, Desak Made; Arini, Novanita Whindi; Yanti, Prima Gusti; Hidayati, Deasy Wahyu; Amzat, Ismail Hussein (Harmoni Sosial: Jurnal Pendidikan IPS, 2024)
This study aims to determine Social Studies (IPS) learning outcomes with a problem-based learning model based on Technological Pedagogical Content Knowledge (TPACK) in elementary school students. The research method used is descriptive quantitative with quasi-experiment. The implementation was carried out in stages with the theory of Borg and Gall, and the main stages are (1) preliminary studies in the form of preparation and needs analysis; (2) preparation of model design and prototype model products in a participatory manner; (3) analysis of trials by learning technology experts; (4) operational trials carried out repeatedly / cycles accompanied by refinement of model products; (5) validation tests using pre-experimental design; and (6) dissemination of results. Data collection in this study was done using objective tests. Observations using observation guideline instruments on activities during the operational test process and pre-experimental tests. Questionnaires and performance assessments were used in the operational and model validation tests. The observation results were analyzed descriptively quantitatively, finding the mean, median, mode, standard deviation, and variance of each variable studied. Data analysis techniques used (1) descriptive analysis, (2) requirements test analysis, and (3) hypothesis testing. The findings of the research showed that elementary school students were motivated to learn by using TPACK-based problem-based learning models and had a high understanding of using ICT learning. The analysis of research results could affect the learning outcomes of social studies based on technological pedagogical content knowledge in elementary schools with an average score of 79.42. So, this research uses classroom action research conducted in 3 (three) cycles. The results obtained up to the third cycle stage (three) were declared complete.